Screening for coronary artery disease among cancer survivors: rationale and design of the REDEEM-CAD study - Cheng Hwee Soh; Joel Smith; Shristy Shrestha; Mark Nolan; Joshua Wong; Nitesh Nerlekar; Thomas H. Marwick (Cardio-Oncology)
Abstract Background Cancer survivors are reported to be at a heightened risk of coronary artery disease (CAD) due to shared risk factors, potentially cardiotoxic cancer treatments and premature aging in survivors. Early identification of those who are at greater risk, followed by protective treatment, can prevent CAD progression. However, to date there was a relative paucity of prospective data to optimally guide management of atherosclerotic coronary risk among cancer survivors. Methods The REDEEM-CAD (Risk-guidEd DisEasE Management plan to prevent CAD in patients with previous cancer) study is a prospective cohort study conducted in Victoria and Tasmania, Australia aiming to evaluate the efficacy of a comprehensive CAD screening strategy. Cancer survivors aged ≥ 40 years with cancer treatment ≥ 5 years prior are eligible for the study. Consented participants will be stratified into low, intermediate or high risk of major atherosclerotic adverse events based on clinical assessment and biochemistry tests. Subsequently, those within the intermediate risk will be referred for coronary artery calcium (CAC) scoring, with computed tomography coronary angiography (CTCA) completed where CAC > 0 and < 400. Participants with high risk or CAC > 400 will be informed about strategies (including lipid-lowering therapy) to manage asymptomatic CAD. Those with low clinical risk or CAC = 0 will conclude their participation while those with CTCA imaged at baseline will be referred for a follow-up CTCA 2-year post-baseline. The primary endpoint is to identify the prevalence of CAD, identified via CAC scoring, among cancer survivors classified as intermediate risk. Secondary endpoint includes the absolute change in total coronary plaque volume over 24 months among those imaged at baseline and follow-up. Summary The REDEEM-CAD study will be the first study to systematically evaluate risk of CAD in cancer survivors, and subsequent responsiveness to coronary risk reduction. This will offer valuable insights into the efficacy of the CAD screening strategies among cancer survivors and the impact of treatment on managing plaque progression. Trial registration NCT05366153.